SISTEM PEMBAGIAN WARISAN BAGI RATA: UPAYA MENGHINDARI PERSELISIHAN ANTAR KELUARGA DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM ADAT - Aziz Siregar, Fatahuddin (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2024)
This study aims to examine the system of equal distribution in the distribution of inheritance applied by the community to avoid disputes between families, with a focus on customary law and Islamic law.  This study uses a qualitative approach to deeply understand the practice of inheritance distribution in society, as well as how customary law and Islamic law are applied in this context. The location of the study is the Muslim community of Aek Marian. The subjects of the study include the head of the family or family members who have been involved in the inheritance distribution process. Data is collected through various techniques to ensure the richness of information and accuracy of research results. The result was the division of inheritance implemented in Aek Marian with a 'equal share' system. There is no distinction between male and female heirs. Boys should get twice the share of girls (An-Nisa: 11). Meanwhile, Article 176 of the KHI explains that boys get twice the share of girls. The equal distribution of inheritance from the perspective of Islamic Law and KHI is not in accordance with the principles set forth in the Qur'an and Hadith. Although this practice occurs due to the influence of customs or family agreements. It is important to consider the legal and social impacts and find solutions that are in line with the sharia to ensure justice and compliance with Islamic law. The distribution of inheritance in equal distribution is not in accordance with the provisions of Faraid and KHI, which has legal impacts and implications in the future.